Pemenuhan Hak Anak Pidana Pada Lembaga Pembinaan Khusus Anak - Loppies, Pricilia Uty Vianty; Toule, Elsa Rina Maya; Wadjo, Hadibah Zachra (Postgraduate Program in Law, Pattimura University, 2024)
Introduction: Protection of children is provided not only by parents but also institutions related to physical and mental development both physically and spiritually. A child who is entered into a Juvenile Correctional Institution is referred to as a criminal child or foster child to get punishment for the actions he has committed, the punishment given is in the form of coaching according to the mandate of the laws and regulations, so that after the criminal or foster child leaves the institution they will no longer commit acts that breaking the law.Purposes of the Research: This study aims to analyze and discuss the fulfillment of the nature of the rights of criminal children and to analyze and discuss the implementation of the rights of criminal children in Ambon Class II Special Development Institutions.Methods of the Research: The type of research used is empirical research. The approach used is legislation, field approach. The sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques through interviews and literature studies. Legal material is qualitativeResults of the Research: The implementation of the rights of criminal children at the Ambon Class II Special Child Development Institution has rights that have been fulfilled and there are rights that have not been fulfilled. The staff of the Ambon Class II Special Child Development Institution are still working on children's rights that have not been fulfilled at the Ambon Class II Special Child Development Institution. The rights of criminal children that have been fulfilled at the Class II Ambon Development Institution, namely: 1) There are facilities for spiritual activities in accordance with religion and beliefs; 2). Correctional students get study rooms, package A, B, C exams, modules and also supporting facilities in the form of computers; 3). criminal children get a reduced sentence through remission, but these provisions must be in accordance with statutory regulations; 4). students get enough food intake; 5). students get visits from family, legal advisers or the community.